Treating double-digit hyponatremia: walking a tight rope - Manjunath Kulkarni; Prashanth Kadri; Raghavendra Bakki Sannegowda; Maria Bethsaida; Nikhil D'Souza (SpringerOpen, 2015)
We report the case of a diabetic patient who presented with severe hyponatremia (serum sodium concentration of 88 mEq/l) caused by hypovolemia and thiazide diuretic use. His serum sodium levels were gradually corrected using a combination of isotonic and hypotonic fluids based on urine output and rate of rise in sodium levels. The patient had complete recovery without any evidence of osmotic demyelination.